2018
DOI: 10.1039/c7cp06681c
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing structural and magnetic properties correlation study on Fe3+-substituted calcium-copper-titanate

Abstract: This communication presents a detailed study on a Fe modified CaCuTiO cubic perovskite system (CaCuTiFeO with x = 0.0-0.7) by performing X-ray powder diffractometry, DC SQUID magnetization and Fe Mössbauer spectroscopy. The first ever Mössbauer studies on the system supported the reported peculiarity of the structure. Mössbauer analysis for the compositions x = 0.1, 0.3, and 0.5 suggest Fe ions in two different environments. The site with larger quadrupole splitting corresponds to Fe in the octahedral symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…CaCu 3 Ti 4 O 12 is a bulk material with a antiferromagnetic behavior below Neel temperature (T N =25 K) studied with neutron diffraction and susceptibility measurements, due to spins (S=1/2) aligned antiferromagnetically on the A sites Cu 2+[56] In order to enhance CCTO magnetic properties and to produce multiferroic material stable at room temperature, many investigations were performed by doping CCTO …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaCu 3 Ti 4 O 12 is a bulk material with a antiferromagnetic behavior below Neel temperature (T N =25 K) studied with neutron diffraction and susceptibility measurements, due to spins (S=1/2) aligned antiferromagnetically on the A sites Cu 2+[56] In order to enhance CCTO magnetic properties and to produce multiferroic material stable at room temperature, many investigations were performed by doping CCTO …”
Section: Applicationsmentioning
confidence: 99%
“…[121] CaCu 3 Ti 4 O 12 is a bulk material with a antiferromagnetic behavior below Neel temperature (T N = 25 K) studied with neutron diffraction and susceptibility measurements, [122] due to spins (S = 1/2) aligned antiferromagnetically on the A sites Cu 2 + [56] In order to enhance CCTO magnetic properties and to produce multiferroic material stable at room temperature, many investigations were performed by doping CCTO. [56,122,123] Wang et al [58] doped CCTO ceramics using Cobalt (Co) by solid-state method. They showed from hysteresis loops, a weak ferromagnetism due to the superexchange interaction along [118]…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…20,29,30 The results are summarized in Table 1 to facilitate the discussion. 20,29,30 The results are summarized in Table 1 to facilitate the discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2000, a large number of research articles discussing theoretical and experimental aspects of fascinating frequency and temperature independent dielectric properties, strong nonlinear I-V characteristics, spectroscopic investigations, intriguing magnetic properties, photocatalytic activity study of pure and substituted perovskite derivative calcium-copper-titanates (CaCu 3 Ti 4 O 12 ) in polycrystalline, nanocrystalline, nanocomposites, single crystalline, and thin film forms are available in the literature. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] A very little number of studies is found on electric (thermoelectric power, dc resistivity, etc), and elastic properties 27,28 of these materials suitable for potential applications such as supercapacitors, varistors, resistive switching memory cells, photoluminescence devices, and gas sensors. 18 Recently, we have carried out positron annihilation spectroscopic investigation of high-energy ball-milling engendered defects in CaCu 3 Ti 4 O 12 , 29 and external stimuli, microwaveassisted heating, rapid thermal cooling, and mechanical milling, induced magnetic ordering in polycrystalline CaCu 3 Ti 4 O 12 quadruple perovskite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation